Synonymy and problematic species of Eiconaxius Spence Bate, 1888, with descriptions of new species (Crustacea: Decapoda: Axiidea: Axiidae) - Poore, Gary C. B. (Zootaxa, 2017)
The genus Eiconaxius Spence Bate, 1888, is rediagnosed. Eiconaxiopsididae Sakai, 2011 and its type genus,                         Eiconaxiopsis Sakai, 2011 are shown to be based largely on an error—the dactylus of pereopod 3 of the type species, Eiconaxiopsis heinrichi Sakai, 2011 is not as was originally illustrated but similar to all other species of Eiconaxius. The synonymies of Eiconaxiopsis with Eiconaxius and Eiconaxiopsididae with Axiidae are confirmed. Eiconaxius faxoni Sakai, 2011 is made an objective junior synonym of Eiconaxius albatrossae Kensley, 1996 (both share the same types). Eiconaxius malaku sp. nov. is erected to replace Eiconaxius indonesicus Sakai, 2011 (nomen nudum). Eiconaxius parvus Spence Bate, 1888 is redescribed based on numerous specimens from Fiji, and Wallis and Futuna. Eiconaxius vaubani sp. nov., which differs from all other species of the genus in the shape of the rostrum and proportions of pereopod 4, is described.